ReActivate—A Goal-Orientated Rehabilitation Program for Adolescent and Young Adult Cancer Survivors. Issue 4 (October 2019) - Smith, Andrew; Murnane, Andrew; Thompson, Kate; Mancuso, Sam
Abstract : Background: Adolescent and young adult (AYA) cancer survivors tend to have poorer physical and mental health outcomes than their healthy peers or survivors of childhood cancer. This study evaluated the feasibility and acceptability of ReActivate, an 8-week, group-based, goal-orientated rehabilitation program for AYA cancer survivors. Methods: A prospective, single-site cohort study was conducted of all AYA cancer survivors who self-referred to the ReActivate program. Participants were 21 (60%) males and 14 (40%) females, who ranged in age from 16 to 25 years ( M = 21.05, SD = 2.62). Weekly group sessions comprised 1 hour of physical activity, followed by 1 hour of education or self-management sessions. The AYAs completed measures assessing physical functioning (ie, cardiovascular fitness, and muscular endurance and strength), psychosocial outcomes (ie, health-related quality of life), and occupational performance. Results: The ReActivate program was found to be feasible and acceptable, with an 87% completion rate and a median attendance rate of 7 sessions (range = 3-8). There were statistically significant increases across most of the physical functioning, health-related quality of life, and perceived occupational performance and satisfaction outcomes, with Cohen's d effect sizes ranging from small to large. Conclusion: The ReActivate program was feasible and acceptable and may have a positive effect on AYA cancer survivors' physical, psychosocial, and occupational functioning. While the findings require replication in a randomized controlled trial, the program has the capacity to optimize delivery of patient care and health resources by bridging the gap that currently exists between the acute and primary care settings. Abstract : Supplemental Digital Content is Available in the Text.